The roles of p38mAPK and caspase-3 in dads-induced apoptosis in human HepG2 cells - Chunxiao Ji (Archives of Biological Sciences, 2010)
The roles of p38MAPK and caspase-3 in DADS-induced apoptosis in human HepG2 cells were investigated. After the human HepG2 cells were treated with DADS, the cell viability, apoptosis and the activity changes of p38MAPK and caspase-3 were measured. The results indicated that DADS can activate p38MAPK and caspase-3. The results showed that p38MAPK and caspase-3 are involved in the process of DADS-induced apoptosis in human HepG2 cells and interact with each other.